Loss of whole chromosome X predicts prognosis of neuroblastoma patients with numerical genomic profile. Issue 5 (28th January 2019) - Parodi, Stefano; Pistorio, Angela; Erminio, Giovanni; Ognibene, Marzia; Morini, Martina; Garaventa, Alberto; Gigliotti, Anna Rita; Haupt, Riccardo; Frassoni, Francesco; Pezzolo, Annalisa
Abstract: Background: Neuroblastoma (NB), a pediatric tumor of the sympathetic nervous system, is characterized by very frequent chromosomal aberrations at the onset of the disease. Identification of further risk factors for relapse, which could lead to increased survival and potentially reduced late effects among survivors, is still urgently needed. Segmental chromosome aberrations (SCA) are associated with poor prognosis, whereas numerical whole‐chromosome aberrations (NCA) are found in patients with a good prognosis; however, a small percentage of the latter patients (10%–15%) subsequently relapse and/or die of disease. Procedure: DNA copy‐number data from 174 NB patients with an NCA genomic profile were analyzed. Association between NCA and event‐free survival (EFS) was investigated by the Kaplan–Meier estimator and prognostic decision tree (DT). Results: DT identified 65 patients with normal chromosome X and an excellent five‐year EFS (100%) independently from the stage at diagnosis. The association between poor EFS and whole chromosome X alterations was confirmed after stratification into two groups of different expected prognosis and by internal validation via bootstrap analysis. Furthermore, the association was also observed in an independent cohort of NB patients extracted from the data set of the National Cancer Institute TARGET Project for Neuroblastoma, but sample size was small ( n  = 75) and statistical significance was not achieved. Conclusions: Loss of whole chromosome X may represent a new prognostic marker for NB patients with an NCA genomic profile. If confirmed by further studies, this finding could indicate that such patients should be reclassified as intermediate risk and treated accordingly.